Case Analysis of Developing Water Treatment Project in Gili Trawangan, North Lombok - Susanto, Yonathan Adiputra; Wandebori, Harimukti (Journal of Business and Management, 2013)
Gili Trawangan is a small island located in north Lombok. Gili Trawangan has a lot of place with beautiful scenery and beach, so it is very potential place for tourism destination. Government is preparing Gili Trawangan to be as famous as Bali. Tourism industry itself had been growing rapidly. Local government plans three big project, those are: building Lombok International Airport, building modern floating dock in Gili Trawangan, and building ring road inside Gili Trawangan. The problem is, infrastructure and supply of clean water are becoming rare commodities. Water is one of the natural resources that control lives of many people. Long time ago, water was one of the natural resources that easily recycled, and clear water was easily to be obtaining everywhere. But nowadays in Gili Trawangan, all ground water has already contaminated by seawater. So, purpose of this project is about producing clean water from seawater and set normal price of clean water. This research describes about list of stakeholders of the project, type of corporation between local government and private company for the project, steps that must be done for realizing this project, kind of technology used in this project, target market, amount of water demand, cost of investment, and financial analysis using cash flow, profit and loss, NPV, IRR, and payback period to find feasibility of project. All data processing is based on collection data from central Biro Pusat Statistik for the population data; and from Ditjen Cipta Karya Dinas Pekerjaan Umum 2006 for water demand calculation. Period of the research is five years that is from 2014 until 2018. Assumption of the initial investment is in 2013.Â Keywords: Water Treatment Project, Gili Trawangan, NPV, IRR, Payback Period.